AdS Ellis wormholes with scalar field - Chen-Hao Hao; Xin Su; Yong-Qiang Wang (European Physical Journal C: Particles and Fields)
Abstract In this paper, we study the spherically symmetric traversable wormholes supported by a phantom field in the anti-de Sitter (AdS) asymptotic spacetime. We couple an additional complex scalar field into this wormhole spacetime and study the physical properties of this model. Despite coupling the scalar matter field, these wormholes remain massless and symmetric for reflection of the radial coordinate $$r → -r.$$ r → - r . The solution possesses a finite Noether charge Q, which varies as a function of frequency $$ω $$ ω with changes in the cosmological constant $$Λ $$ Λ and the throat size $$r_0.$$ r 0 . Under specific conditions, an approximate “event horizon” will appear at the throat.